FAKTOR INTRINSIK YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN PADA KLIEN YANG TERPASANG TERAPI CAIRAN INTRAVENA DI RUANGAN ASOKA BOUGENVILLE RS TK. III R.W. MONGISIDI MANADO - Suprapta, I Gusti Ngurah; Bidjuni, Hendro; Karundeng, Michael (JURNAL KEPERAWATAN, 2015)
ABSTRACK: Preliminary Anxiety is happening on the medical action can affect the health of the patient and family. One medical treatment procedures such as the installation of intravenous fluid therapy can bring anxiety within the client because there is the threat of bodily integrity. The purpose this study was to determine the factors associated with the level of anxiety in patients who mounted intravenous fluid therapy in the hospital room Asoka Bougenville Tk. III R.W. Monginsidi Manado. Research design used is descriptive cross sectional analytic approach. Sample 43 respondents. Determination of the sample by using total sampling. The statistical test used Chi-Square with significance level Î± = 0.05. Results obtained: there is a relationship between therapeutic communication with the patient's anxiety level, there is a relationship between the length of time the patient's anxiety level, and there is a relationship between the degree of discomfort with the level of anxiety in patients who mounted intravenous fluid therapy. Conclusion There is a significant relationship between communication trapeutik, duration and degree of discomfort attached to the patient's level of anxiety attached to intravenous fluid therapy. Suggestion of the results expected for nurses as implementing nursing care should pay more attention to the basic needs of patients, especially providing interventions for pain relief or restore comfort to simultaneously reduce patient anxiety. Keywords : Intravenous Fluid Therapy, Anxiety ABSTRAK: Pendahuluan Kecemasan yang terjadi atas tindakan medis dapat mempengaruhi kesehatan pasien dan keluarga. Salah satu prosedur tindakan medis seperti pemasangan terapi cairan intravena dapat mendatangkan kecemasan dalam diri klien karena terdapat ancaman integritas tubuh. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan pada klien yang terpasang terapi cairan intravena di Ruangan Asoka Bougenville RS Tk. III R.W. Mongisidi Manado. Desain penelitian yang digunakan adalah Deskriptif analitik dengan pendekatan Cross sectional. Sampel 43 responden. Penentuan besar sampel dengan menggunakan total sampling. Uji statistik yang digunakan adalah Chi-Square dengan tingkat kemaknaan Î±=0,05. Hasil Penelitian diperoleh: ada hubungan antara komunikasi terapeutik dengan tingkat kecemasan klien, ada hubungan antara lama waktu dengan tingkat kecemasan klien, dan ada hubungan antara derajat ketidaknyaman dengan tingkat kecemasan pada klien yang terpasang terapi cairan intravena. Kesimpulan Terdapat hubungan yang signifikan antara komunikasi trapeutik, lama waktu terpasang dan derajat ketidaknyamanan dengan tingkat kecemasan klien yang terpasang terapi cairan intravena. Saran dari hasilpenelitian diharapkan bagi perawat sebagai pelaksana asuhan keperawatan harus lebih memperhatikan kebutuhan dasar klien terutama memberikan intervensi untuk menghilangkan nyeri atau mengembalikan kenyamanan sehingga secara bersamaan menurunkan tingkat kecemasan klien. Kata Kunci : Terapi Cairan Intravena, Kecemasan